Chromatin-associated cullin-RING E3 ubiquitin ligases: keeping transcriptionally active NF-κB in check - Gong, Mengyao; Luo, Junqi; Liang, Qiankun; Liu, Yi; Zheng, Yuejuan; Yang, Xiao-Dong (Frontiers in Immunology, 2025)
Nuclear factor-κB (NF-κB) constitutes a family of transcription factors that serve as a critical regulatory hub, dynamically orchestrating inflammatory and immune responses to maintain homeostasis and protect against pathogenic threats. Persistent activation of NF-κB has been implicated in the pathogenesis of various inflammatory diseases and cancer. A critical mechanism to prevent excessive inflammation and its harmful effects is the timely termination of NF-κB’s transcriptional activity on target genes. This termination can be facilitated through the ubiquitination and subsequent proteasomal degradation of chromatin-bound RelA, the most active subunit of NF-κB. Several multi-subunit cullin-RING E3 ubiquitin ligases, composed of elongin B/C, cullin2/5, and SOCS-box proteins, have been identified to target RelA for degradation. These E3s, known as ECS complexes, use SOCS-box proteins as substrate-recognizing subunits to engage RelA. SOCS1 is the first identified SOCS-box member that functions in ECSSOCS1 to target chromatin-bound RelA for ubiquitination. Specifically, SOCS1 collaborates with accessory proteins COMMD1 and GCN5 to preferentially recognize Ser468-phosphorylated RelA. Our recent work demonstrates that WSB1 and WSB2 (WSB1/2), two additional SOCS-box proteins with structurally similar WD40 repeat domains, function as substrate-recognizing subunits of ECSWSB1/2 to specifically mediate the ubiquitination and degradation of chromatin-associated RelA methylated at Lys314/315. In this review, we summarize the discovery and functional importance of ECSSOCS1 and ECSWSB1/2 in terminating NF-κB activity, highlight the distinct molecular mechanisms by which they ubiquitinate chromatin-associated RelA in a modification- and gene-specific manner, and discuss their potential as therapeutic targets for inflammatory diseases and cancer.